THE EFFECT OF GROUP DISCUSSION METHOD ON STUDENT LEARNING OUTCOMES AT SMP N 21 PONTIANAK - Fatmayani, Dewi; Matsum, Junaidi H; Buwono, Sri (Universitas Tanjungpura, 2023)
This study aims to determine how much the influence of the use of the discussion method on the Learning Outcomes of Students in Social Studies Subjects for class VIII at SMP Negeri 21 Pontianak. The method used in this study was a quantitative approach with descriptive research type (relationship study). The variables researched (X) with (Y). Based on the data analysis, the researchers concluded that: 1) The use of the Group Discussion Method for class VIII had a moderate category with data acquisition as many as 30 (67.4%) students in thatcategory. 2) Social Studies Subject Learning Outcomes obtained from the data processing results obtained as many as 33 (64.71%) students In the medium category who obtained learning outcomes more than the Maximum Completeness Criteria (KKM). 3) The magnitude of the influence of the use of the Group Discussion Method on the Learning Outcomes of Social Studies Subjects Class VIII SMP Negeri 21 Pontianak resulted in the value of t count â‰¥ t table (3,685â‰¥2,010) thus Ho was rejected and Ha was accepted. Based on the R2 test, it was obtained that the magnitude of the effect of using the group discussion method on learning outcomes was 20.1%.